2005
DOI: 10.1001/archsurg.140.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Is a Risk Factor for Incisional Hernia

Abstract: Hypothesis: A number of risk factors for incisional hernia have been identified, but the pathogenesis remains unclear. Based on previous findings of smoking as a risk factor for wound complications and recurrence of groin hernia, we studied whether smoking is associated with incisional hernia. Design: Cohort study. Clinical follow-up study for incisional hernia 33 to 57 months following laparotomy for gastrointestinal disease. Variables predictive for incisional hernia were assessed by multiple regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
161
1
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(177 citation statements)
references
References 46 publications
5
161
1
10
Order By: Relevance
“…However, in another study, the wound infection rate in smokers was 12% compared with 2% in never-smokers (Sorensen et al 2003). Smoking, increase the risk of wound infection presumably through reduction of the oxidative killing mechanism of neutrophils (Sorensen et al 2005).…”
Section: Resultsmentioning
confidence: 92%
“…However, in another study, the wound infection rate in smokers was 12% compared with 2% in never-smokers (Sorensen et al 2003). Smoking, increase the risk of wound infection presumably through reduction of the oxidative killing mechanism of neutrophils (Sorensen et al 2005).…”
Section: Resultsmentioning
confidence: 92%
“…These include patient factors such as diabetes, COPD, abdominal aortic aneurysm, smoking, high BMI and peri-operative factors such as emergency surgery, duration of surgery, blood transfusion and surgical site infection. [2][3][4][5] Our aim, in this retrospective cohort study, was to ascertain any particular factors that lead to the development of a ventral incisional hernia post laparotomy. Through identification of risk factors, we can modify these risk factors in the perioperative period in order to try to reduce the risk of development of VIH.…”
Section: Introductionmentioning
confidence: 99%
“…Age (>50) did not have an effect. Sorensen et al (9) found an association with older age and male gender and the formation of a hernia in a series of 916 patients. However, other studies did not find a significant relation with gender and hernia formation (8).…”
Section: Discussionmentioning
confidence: 96%